The Impact of Digital Competence on Language Instruction Among Early Childhood Development and Education Teachers in Eastern Kenya - Moses, Oyieno Ouma; Kangara, Hannah; Ogembo, John; Ituma, Monica (Universitas Pendidikan Ganesha, 2024)
Digital competence among Early Childhood Development and Education (ECDE) teachers is crucial for integrating learning within ECDE units, which requires the availability and effective utilization of digital resources in the instructional process. This study aimed to analyze the relationship between ECDE teachers' digital competence and language instruction in the upper Eastern Counties of Kenya. A mixed-methods approach was employed, utilizing both descriptive survey and correlational research designs. A sample of 365 respondents, including 181 language teachers, 181 head teachers, and 3 ECDE County Directors, was drawn from a population of 4,021. Data were collected using questionnaires and interview schedules, with a response rate of 93.15% (339 respondents). Qualitative data were analyzed thematically, while quantitative data were analyzed using descriptive and inferential statistics with the assistance of SPSS version 27.0 software. Frequencies and percentages described the existing relationships between study variables, and hypotheses were tested using logistic regression at a 95% confidence level. The findings revealed that teachers' digital competence has a positive and significant relationship with language instruction. Based on these results, the study recommends targeted training and professional development programs to enhance ECDE teachers' digital proficiency, thereby improving their ability to effectively utilize digital resources in language instruction.